Synthesis, Crystal Structure, Mesophase Behaviour and Optical Property of Azo-ester Bridged Compounds: Azo-ester Bridged Compounds - Karim, M. R.; Sheikh, M. R. K.; Islam, M. S.; Salleh, N. M.; Yahya, R. (Journal of Scientific Research, 2019)
Azo-ester mesogen containing two liquid crystalline compounds C1-C2 having polymerizable acrylate functional group as the terminal were designed and synthesized. The chemical structures and purity of the synthesized compounds were confirmed by different spectroscopic techniques such as FT-IR, 1H NMR and 13C NMR. X-ray crystal structure showed that compound C1 exhibited more stable E configuration with two bulky groups in the opposite sides of the N=N double bond motifs. The 1, 2-diphenyldiazene fragment in the structure of C1 is essentially planar with RMS deviation from planarity of 0.0555 Å. Analysis of the crystal packing of compound C1 revealed its intriguing supramolecular sheet-like multilayer molecular packing stabilized by C-H…O interaction involving the phenyl and acryloyl hydrogen with the carbonyl oxygen and alkoxy oxygen atoms. Thermogravimetric investigation demonstrated that both of the compounds exhibited excellent thermal stability and their thermal degradation was influenced by the terminal substituent. The DSC and POM studies confirmed that compounds C1-C2 exhibited enantiotropic liquid crystalline mesophase behaviour. Optical investigations demonstrated that both of the compounds showed strong absorption band around 300-420 nm and exhibited blue fluorescence emission.